2019
DOI: 10.1111/1751-2980.12751
|View full text |Cite
|
Sign up to set email alerts
|

What are the main areas of focus to prevent or treat non‐alcoholic fatty liver disease?

Abstract: Recently, a growing body of information has accumulated to suggest that nutritional status and food compounds impact on the development or progression of nonalcoholic fatty liver disease (NAFLD). The best strategy to prevent and treat NAFLD is to modify diet and lifestyle by maintaining a healthy weight, following a wellbalanced diet with appropriate energy intake and increasing physical activity or strength training. Here we review the literatures and discuss existing and potential therapeutic strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
2
0
2
Order By: Relevance
“…Metformin, a treatment option of choice for T2DM, has been shown to lessen steatosis in individuals with NASH and to avoid liver events in T2DM patients with advanced NASH [ 21 ]. Liraglutide has been shown in studies to have a favorable impact on NASH and the development of fibrosis by lowering body weight, even in patients who do not have T2DM [ 42 ]. The thiazolidinediones group, which includes the peroxisome proliferator-activated receptor (PPAR) agonists rosiglitazone and pioglitazone, has anti-steatotic, anti-inflammatory, and to a lesser extent, therapeutic benefits in NAFLD [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, a treatment option of choice for T2DM, has been shown to lessen steatosis in individuals with NASH and to avoid liver events in T2DM patients with advanced NASH [ 21 ]. Liraglutide has been shown in studies to have a favorable impact on NASH and the development of fibrosis by lowering body weight, even in patients who do not have T2DM [ 42 ]. The thiazolidinediones group, which includes the peroxisome proliferator-activated receptor (PPAR) agonists rosiglitazone and pioglitazone, has anti-steatotic, anti-inflammatory, and to a lesser extent, therapeutic benefits in NAFLD [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Liraglutide has been shown in studies to have a favorable impact on NASH and the development of fibrosis by lowering body weight, even in patients who do not have T2DM [ 42 ]. The thiazolidinediones group, which includes the peroxisome proliferator-activated receptor (PPAR) agonists rosiglitazone and pioglitazone, has anti-steatotic, anti-inflammatory, and to a lesser extent, therapeutic benefits in NAFLD [ 42 ]. In a phase 2 study, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) showed improvement in liver histology in individuals with NASH [ 20 ], in addition to improvement in cardiovascular and all-cause mortality in high-risk T2DM patients.…”
Section: Reviewmentioning
confidence: 99%
“…À ce jour, il n'y a aucune thérapie pharmacologique autorisée pour traiter la SHNA. Cependant, plusieurs interventions ont été proposées pour la maîtriser (tableau 1) (7). Ces dernières mettent l'accent sur les modifications des habitudes de vie.…”
Section: Stratégies Thérapeutiquesunclassified
“…Interventions proposées pour la gestion de la stéatose hépatique non alcoolique (adapté de Mansour et coll. 2019 (7))…”
Section: Définition Et Origine De La Diète Cétogèneunclassified